DEVELOPMENT OF TEACHER PROFESSIONALISM IN GENERAL EDUCATION: CURRENT TRENDS AND FUTURE DIRECTIONS - Novianty Djafri; Akhmadi; Siska Dwi Yulianti; Opan Arifudin; Iwan Ridwan (International Journal of Teaching and Learning, 2024)
Teachers play a strategic role in creating quality human resources. Every effort made to improve the quality of human resources without involving teachers will end in difficulties because teachers are the key people in determining the quality of education. Therefore, teachers are expected to have professionalism by mastering pedagogical, professional, social and personal competencies. One of the latest trends in the development of teacher professionalism is the adoption of technology in learning. Creative teachers use various applications and online platforms to enhance students' learning experience. They leverage learning videos, online forums, and even social media to facilitate collaboration and knowledge sharing. In this article, several strategies have been explained that teachers can use to increase their professionalism. By implementing these strategies, it is hoped that teachers can become more professional in carrying out learning tasks and create a conducive classroom atmosphere for students.